Application Of The Steam Approach To Increase Learning Outcomes For Theme 4 Students Of Class IVb Sd Negeri 0411 Pasar Ujung Batu T.P 2020/2021 - Megaria Sihombing; Eni Marta (STKIP Rokania Pasir Pangaraian, 2021)
The background of this research is the low student learning outcomes which are marked by the number of student scores who have not reached the KKM, this is because the method used by the teacher does not attract the attention of students. The purpose of this study was to determine the improvement of learning outcomes in theme 4 through the STEAM approach to the fourth grade students of SD Negeri 0411 Pasar Ujung Batu. This research is classroom action research which consists of 2 cycles, namely cycle I and cycle II. The data sources in this study were the fourth grade students of SD Negeri 0411 Pasar Ujung Batu, totaling 25 students in the 2020/2021 school year and the sample was determined by the entire population. The data are the results of the initial test, the results of the final test. Data analysis techniques through quantitative and qualitative approaches. The results of the initial test in this study obtained a percentage (34.7%) in the first cycle (60.9%) and (100%) in the second cycle. It was concluded that the STEAM approach could improve the learning outcomes of fourth graders at SD Negeri 0411 Pasar Ujung Batu on theme 4